Selling and sales management - Jobber, David, 1947-; Lancaster, Geoffrey, 1938-; Le Meunier-FitzHugh, Kenneth (Harlow: Pearson, 2019)
"The definitive text that connects sales theory to the practical implications of selling in today's world. Selling and Sales Management, 12th Edition, by Jobber, Lancaster and Le Meunier-FitzHugh provides an integrated and strategic approach to managing sales and customer relations in a complex, volatile and global marketplace. Fully updated with latest case studies and practical exercises, the new edition covers leading research into the use of technology to enhance the selling process, as well as the recent thinking in customer relationship management and the interactions between sales and marketing functions. The text is well grounded for undergraduate and postgraduate students in business management or marketing degrees, as well those studying MBA or sales professionals in the field. The new edition offers Expanded coverage of the management of sales channels, Updated content on the role of social media and AI in selling, Increased coverage of strategic selling and partnering, Discussion on the interactions between sales and marketing functions, Updated coverage of the management of sales channels and Extended discussion on customer management"--
Includes bibliographical references and index.